2008
DOI: 10.1007/s00415-008-0677-1
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure in acute ischemic stroke

Abstract: Both forms of HF (with or without decreased systolic function) are associated with poor outcome in AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 29 publications
6
70
2
3
Order By: Relevance
“…Clinical factors such as age, stroke severity, atrial fibrillation (AF), female sex, diabetes, and congestive heart failure (CHF) have been associated with poor prognosis after an ischemic stroke (IS) [21,26]. In addition, AF is the main cause of IS in the elderly and is associated with a high mortality and disability rate [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical factors such as age, stroke severity, atrial fibrillation (AF), female sex, diabetes, and congestive heart failure (CHF) have been associated with poor prognosis after an ischemic stroke (IS) [21,26]. In addition, AF is the main cause of IS in the elderly and is associated with a high mortality and disability rate [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Atrial Fibrillation Clopidogrel Trial with Irbesartan for Prevention of Vascular Events (ACTIVE) trial showed that a risk of embolic event was similar in heart failure with systolic dysfunction (4.4%) and DD (4.3%) [32] . Two studies have shown that heart failure with preserved ejection fraction is prevalent and independently related to poor prognosis after ischemic stroke although they did not directly evaluate diastolic function [3] . In line with previous reports, our data showed that DD is prevalent in stroke patients and is associated with post-stroke outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DD is related to mortality in patients with myocardial infarct and septic shock [5,6] . With regard to ischemic stroke, only one study showed that DD is associated with moderate to severe functional disability at 3 months after stroke with a relative risk of 2.5 [3] . However, this study was constrained because DD was defined if the patient had heart failure symptoms with normal ejection fraction ( ≥ 50%) [3] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations